Spatially modulating interfacial properties of transparent conductive oxides patterning work function with phosphonic Acid self-assembled monolayers - Knesting, Kristina M (Advanced materials (Deerfield Beach, Fla.), 2012)
Copyright © 2012 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.